Early Postoperative Pain Predicts 2-Year Functional Outcomes following Knee Arthroplasty - Lakra, Akshay; Murtaugh, Taylor; Shah, Roshan P.; Cooper, H. John; Geller, Jeffrey A. (The Journal of Knee Surgery, 2019)
Pain control following knee arthroplasty is extremely important to both patients and surgeons to improve the perioperative experience; however, the implication of early pain control on long-term outcomes following knee arthroplasty remains poorly understood. We hypothesized that poor early pain control results in poor functional outcomes 2 years following total (TKA) and unicondylar knee arthroplasty (UKA). This retrospective study reviewed 242 TKA and 162 UKA performed at a single institution by two surgeons. Mean visual analog scale (VAS) pain scores were collected for first 3 postoperative days. Patients were prospectively evaluated using short form (SF-12), the Western Ontario and McMaster University osteoarthritis index (WOMAC), and the Knee Society functional score (KSFS) questionnaires. Pearson's correlation coefficients were calculated between mean VAS pain scores and functional outcome scores at 2 years. In the TKA group, poorly controlled perioperative pain correlated with poorer functional scores at 2 years. There was a significant negative correlation between early mean VAS pain scores (mean, 3.2 ± 2.0) and most 2-year functional outcomes including SF-12 physical score (r = −0.227, p ≤ 0.01), WOMAC pain scores (r = −0.268, p ≤ 0.01), WOMAC stiffness scores (r = −0.224, p < 0.01), WOMAC function score (r = −0.290, p 0.01), and KSFS (r = −0.175, p = 0.031). Better control of early pain was associated with improved functional outcomes at 2 years following TKA. We also found significant negative correlations between preoperative functional scores and early postoperative pain scores. Collectively, using preoperative and early postoperative pain scores, we identified an “at-risk” patient group that manifested an inferior functional outcome at 2 years; these patients may benefit from closer surveillance and a multidisciplinary approach to pain and function to optimize their clinical outcome following knee arthroplasty.
Keywords: total knee arthroplasty; VAS pain scores; unicondylar knee arthroplasty; functional outcomes; pain